การจัดการชุมชนสัมพันธ์ของผู้ประกอบการธุรกิจโรงแรม - รัชนิกร สำราญรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objectives of the research are (1) to study the community relations management of the hotel industry, (2) to study media exposure of community relations, attitude and participation in the community relations activities and (3) to study the relationship between the media exposure, attitude and the participation of the community relations activities. These research methods are the qualitative research with in-depth interviewing with persons who involved in community relations program of the hotel, documentary and quantitative research, a survey research of 400 residents nearby the hotels. The result shows that the community relations of the hotel have been well developed continually. The community relations management of the hotel has been systematically and methodically managed. The targets of the community relation activity are the community as per geography and the community as per the issue. The media mixed is the main media strategy, the strategy for relationship building is the informal communication and the friendliness. The evaluation is the combination between the formal evaluation by the staff meeting and the informal evaluation by the observation during the activity. The factor to support and to obstruct the effectiveness of the community relations activities are the internal factors and external factors. In term of media exposure of community relations activities, attitude and participation in the community relations activities, the result shows that the exposure of the community is low, mainly exposure to the personal source. The attitude to the hotel and the community relations activity of the community is average. The participation in the community relations activity of the community is in the low level. The media exposure of community relations has positive correlation with the community’s attitude. The media exposure of community relations has positive correlation with the community’s participation. The community’s attitude has the positive correlation with the community’s participation.